2019
DOI: 10.1002/hed.25935
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the depth of invasion in superficial pharyngeal cancer: Microvessel morphological evaluation with narrowband imaging

Abstract: Background Magnifying endoscopy with narrowband imaging (ME‐NBI) is useful in predicting the invasion depth by examining the microvascular status of tumor surfaces. This retrospective study aimed to determine its efficacy in pharyngeal cancer. Methods Between April 2016 and March 2018, 59 lesions from 46 patients who underwent transoral resection were retrospectively analyzed. Using ME‐NBI, microvascular status was classified into B1, B2, or B3, based on the classification of the Japan Esophageal Society. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The findings of previous reports on ME‐NBI for pharyngeal cancer are summarized in Table 6 . 17 , 19 , 20 , 21 , 22 , 23 Pharyngeal carcinoma with B2–B3 vessels has been reported to be significantly more likely to show SEP. 17 , 21 Furthermore, there are a few reports on the correlation between B vessels and tumor thickness. 22 , 23 In this study, the tumor thickness was significantly greater in the order of B1, B2, and B3 vessels, suggesting that the thickness of the tumor, which may be a risk factor for LNM, can be predicted by observing the microvascular pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of previous reports on ME‐NBI for pharyngeal cancer are summarized in Table 6 . 17 , 19 , 20 , 21 , 22 , 23 Pharyngeal carcinoma with B2–B3 vessels has been reported to be significantly more likely to show SEP. 17 , 21 Furthermore, there are a few reports on the correlation between B vessels and tumor thickness. 22 , 23 In this study, the tumor thickness was significantly greater in the order of B1, B2, and B3 vessels, suggesting that the thickness of the tumor, which may be a risk factor for LNM, can be predicted by observing the microvascular pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed a statistically significant association between tumor thickness and CLNM (Table 3). As predictors for tumor thickness, Eguchi et al have demonstrated a significant correlation between the classification of type B vessels and tumor thickness in superficial pharyngeal cancer (20). Katada et al also have reported on the substantial correlation between the classification of type B vessels and synchronous lymph node metastasis/lymphatic invasion in superficial pharyngeal cancer (21).…”
Section: Association Between Tumor Thickness and Classification Of Ty...mentioning
confidence: 99%
“…Additionally, we classified the depth of invasion in SHNC as either EP (tumor located in the epithelium, equivalent to carcinoma in situ) or SEP (tumor involving the subepithelial layer). Tumor thickness, defined as the distance from the tumor surface to the deepest point of tumor invasion (3,20,21), was measured in the SEP tumors.…”
Section: Analysis Of Predictive Factorsmentioning
confidence: 99%
“…NBI is highly powerful, not only in differentiating nonmalignant from malignant lesions (34), but also in detecting precancerous lesions and predicting the invasive depth and thickness of pharyngeal tumors (35)(36)(37). To date, the classifications include IPCL Pattern Classification, namely, the Japan Esophageal Society Classification (JES Classification), and the NBI Classification of nasopharyngeal mucosal microvessel patterns.…”
Section: The Classifications Of Pharyngeal Lesionsmentioning
confidence: 99%
“…The Ni Classification has been used for the early diagnosis of head and neck squamous cell carcinomas (HNSCCs) and this classification also shares some common criteria with the JES Classification. Eguchi found that Va and Vb of the Ni Classification corresponded to the B1 and B2 Classification, respectively (28,36,(39)(40)(41).…”
Section: The Classifications Of Pharyngeal Lesionsmentioning
confidence: 99%